Synchronous self-assessment: First experience for higher education instructors - Remesal, Ana; Estrada, Flor G. (Frontiers in Education, 2023)
We present a qualitative study of four cases of university instructors (teacher educators) implementing synchronous self-assessment (SSA). SSA consists of an innovative assessment strategy during written exam situations, which highlights the students’ voice and agency, giving it greater weight in the power balance traditionally established between instructors and students in classroom assessment practices. In this article, we focus on the effects and pedagogical potential of this assessment strategy from instructors’ point of view. In our study, three instructors were novels in implementing this strategy; the fourth instructor had several years of experience with it. The four instructors agreed on basic design features for an end-of-semester exam offered in four groups of first-year students of the same shared program at a Bachelor’s degree for Kindergarten Educator and Primary School Teacher. The instructors were individually interviewed after the assessment session in their course and the exams were gathered for analysis. Content and discursive analysis was carried out on the data. Results show substantial differences in the evaluative artefacts (instructors’ exams) in terms of cognitive demand and formative assessment potential, and point to noticeable needs for professional development in pursuit of assessment literacy in Higher Education.